1988
DOI: 10.1093/ajcn/48.2.298
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of beta-carotene in humans

Abstract: Normal healthy volunteers were studied after they ingested various beta-carotene doses. Daily administration of 15 or 45 mg beta-carotene resulted in significant increase in plasma beta-carotene levels. The extent of increase and the pattern of plasma beta-carotene levels showed substantial interindividual variation. Absorption of beta-carotene was affected by dietary fat concentration. Individuals placed on a high-fat diet showed significant increases in plasma beta-carotene as compared with those placed on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
2

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(107 citation statements)
references
References 23 publications
2
103
0
2
Order By: Relevance
“…Another way of reducing matrix effects is by homogenization or particle size reduction (van Zeben & Hendriks, 1948;Gärtner et al, 1997;Castenmiller et al, 1999;van het Hof et al, 1999). Dietary fat, as well, has a documented positive effect on bioavailability of carotenoids (Roels et al, 1958;Dimitrov et al, 1988;Shiau et al, 1994;Jalal et al, 1998), although the amount of fat required to optimize carotenoid bioavailability has not been clearly identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way of reducing matrix effects is by homogenization or particle size reduction (van Zeben & Hendriks, 1948;Gärtner et al, 1997;Castenmiller et al, 1999;van het Hof et al, 1999). Dietary fat, as well, has a documented positive effect on bioavailability of carotenoids (Roels et al, 1958;Dimitrov et al, 1988;Shiau et al, 1994;Jalal et al, 1998), although the amount of fat required to optimize carotenoid bioavailability has not been clearly identified.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly applied method includes measuring increases in plasma concentrations of carotenoids or retinol in humans following administration of an acute or chronic dose of an isolated carotenoid or a carotenoid-containing food (Brown et al, 1989;Micozzi et al, 1992;Castenmiller et al, 1999;van het Hof et al, 1999). This is a relative measure, as the plasma is highly dynamic and individual responses have been reported to be highly variable (Dimitrov et al, 1988;Törrönen et al, 1996). To obtain a quantitative measure of carotenoid bioavailability, the oral -faecal balance method is a better approach (Roels et al, 1958;Shiau et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Other carotenoids and alpha-tocopherol levels also indicate no major differential effect, although the large s.d.s mean that small differences cannot be excluded. Previous studies that suggested a significant role of fat in the bioavailability of beta-carotene had compared no fat meals with meals cooked in fat (Dimitrov et al, 1988;Prince & Frisoli, 1993). Also, these studies were of short duration F 5 days (Dimitrov et al, 1988) or a single dose test (Prince & Frisoli, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The intake of carotenoid-rich foods cooked with oil increases the serum carotenoid bioavailability (Stahl & Sies, 1992). The effects of different amounts of oil in the diet on the serum concentration of beta-carotene (Jayarajan et al, 1980;Dimitrov et al, 1988;Jalal et al, 1998) and lutein (Roodenburg et al, 2000) have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Dimitrov et al 27 constataram que a absorção de β-caroteno é afetada pela concentração de gordura da dieta. Ao receberem uma dieta hiperlipídica, indivíduos saudáveis apresentaram significante elevação na concentração plasmática de β-caroteno quando comparados aos indivíduos que receberam uma dieta hipolipídica.…”
Section: Fatores Influentes (Slamenghi)unclassified